Does being mindful make people more creative at work? The role of creative process engagement and perceived leader humility - Cheung, Siu Yin; Huang, Emily G.; Chang, Song; Wei, Liqun (Organizational Behavior and Human Decision Processes, 2020)
An emerging line of research in the mindfulness literature is to examine the role of mindfulness in creativity in organizations. Thus far, little is known about how and when mindfulness, defined as present-moment attention, is associated with employee creativity. We theorize and test a model that links mindfulness to employee creativity through creative process engagement. We further suggest and test perceived leader humility as a boundary condition for such an association. The results of two field studies with time-lagged designs provide supporting evidence for our conceptual model. Specifically, the findings from both studies indicate that employee mindfulness has a positive association with supervisor-rated employee creativity through employee creative process engagement. In our second study, we also find that the indirect positive association between mindfulness and employee creativity (via creative process engagement) is strengthened when employees perceive their supervisors to be humble leaders. In contrast, the conditional indirect relationship is statistically nonsignificant under the condition of low perceived leader humility.